Tests collection for pathophysiology practical classes - Kolesnik, Y. M.; Melnikova, O. V.; Колесник, Юрій Михайлович; Мельнікова, Ольга Валеріївна (Zaporozhye state medical university, 2015)
Tests collection on pathophysiology is proposed for the students of the 3rd course medical student for better individual preparation for practical classes, submodules and module controls on pathophysiology according to the program of education. Tests included in this collection are of single type – with one best variant of answer. This test type is also used in state licensing examination “Krok 1 – general medicine”.
Keywords: pathophysiology; патофізіологія; патофизиология